FRI0337 Anca pattern in granulomatosis with polyangitis and micropolyangitis. a retrospective analysis on a multicentric inception cohort. (15th June 2017) - Felicetti, M; Padoan, R; Monti, S; Berti, A; Paolazzi, G; Brunori, G; Caporali, R; Schiavon, F
Abstract : Background: Granulomatosis with polyangiitis (GPA) and microscopic polyangiitis (MPA) are multi-systemic diseases associated with anti-neutrophil cytoplasmic antibody (ANCA) often characterized by overlapping clinical manifestations. Recently ANCA pattern has been reported to define different clinical manifestations and long-term outcomes1. Objectives: To analyze how ANCA could influence clinical manifestations and long-term outcomes in ANCA-associated vasculitis (AAV) patients, previously classified as GPA or MPA, from three different referral centers of Northern Italy. Methods: Clinical manifestations and long-term outcomes of GPA and MPA patients were retrospectively collected. We considered clinical (including BVASv3 and VDI), radiological and histological data at diagnosis, relapse and mortality rates at the last follow-up. The complete cohort was splitted into three groups based on ANCA (anti-myeloperoxidase (MPO), anti-proteinase 3 (PR3), and ANCA negative) for statistical analysis. Results: We included 171 patients, 90 (52.6%) anti-PR3 positive, 52 (30.4%) anti-MPO positive and 25 (14.6%) ANCA negative. Patients were mainly middle aged (52.5±15.9 years), Caucasian (98.2%) and both sexes were equally represented (Female 53.2%). Anti-MPO positive patients were older (65 [52.5–69.7] years) at disease onset (p<0.001), affected by more comorbidities (p=0.045). They presented more frequently renal involvement (p<0.001) with higher creatinine levels at diagnosis (0.98 [0.75–1.92] mg/dL, p<0.001) (Fig. 1 ), systemic symptoms (p=0.039) but lower frequency of upper airways involvement (p=0.005). Anti-PR3 positive scored higher BVASv3 at onset (p<0.001) and presented more upper airways involvement (p=0.033), lung nodules (p=0.002) and skin purpura (p=0.016). ANCA negative showed a longer diagnostic latency (8.5 [3.5–49] months, p<0.0001), they presented with a higher VDI at diagnosis (1 [0–2.7], p<0.0001) and the highest frequencies of sinuses (p=0.031), laryngeal (p=0.026) and CNS (p=0.020) involvement. Long-term outcomes were available only in 113 patients. A low long-term mortality rate (8, 7.1% deaths) was noted (mean follow-up of 66.6±30.6 months), significantly higher in anti-MPO positive patients 7 (21.9%) when compared to anti-PR3 positive 1 (1.6%) and ANCA negative 0 (0%) (p<0.001). Nevertheless, the highest number of relapses/years were associated with anti-PR3 positivity (0.7±1.3 vs 0.1±0.3 in anti-MPO and 0.4±0.7 in ANCA negative, p=0.012). At multivariate analysis, anti-PR3 pattern resulted an independent predictive factor of relapses (p=0.0036, OR 5.8, IC95%: 1.1–29). Conclusions: Our study confirms the hypothesis that each ANCA pattern could define a specific disease subset with different clinical manifestations and outcomes in AAV. Furthermore, in our cohort we observed a lower rate of recurrence and a better long term survival (92.9%) than in literature. References: Mahr A et al; French Vasculitis Study Group (FVSG) and the European Vasculitis Society (EUVAS): Revisiting the classification of clinical phenotypes of anti-neutrophil cytoplasmic antibody-associated vasculitis: a cluster analysis. Ann Rheum Dis. 2013 Jun;72(6):1003–10. Disclosure of Interest: None declared